Delayed diaphragmatic rupture presenting with acute gastric volvulus - Williamson, JML (Ann R Coll Surg Engl, 2014)
Gastric volvulus is a rare complication of diaphragmatic rupture. We report the case of an 82-year-old man who presented following an out-of-hospital cardiac arrest. Chest radiography and thoracic computed tomography revealed an acute gastric volvulus and a chronic diaphragmatic hernia containing transverse colon and abdominal viscera. He had complained of retching and associated epigastric pain prior to collapse, and had sustained a motorcycle accident approximately 60 years earlier. Insertion of a nasogastric tube was unsuccessful (completing Borchardt’s diagnostic triad) and his condition prevented both operative and endoscopic reduction of his volvulus. He died soon afterwards.